Kelayakan Buku Saku Elektronik “Mangifera di Bantaran Sungai Desa Beringin Kencana” sebagai Materi Pengayaan Konsep Keanekaragaman Hayati - Syifa Fauzia; Hardiansyah Hardiansyah; Mahrudin Mahrudin (Wahana-Bio: Jurnal Biologi dan Pembelajarannya, 2022)
Research and development is oriented towards field data. The results of the field research were then developed into an HTML 5-based electronic pocket book. The electronic pocket book contains Mangifera diversity on the riverbanks of Beringin Kencana Village as material for enriching the concept of biodiversity. The aim of the study was to describe the feasibility of the electronic pocket book "Mangifera on the Riverbanks of Beringin Kencana Village" as material for enriching the concept of Biodiversity in SMA. Research and development used the Borg and Gall model. The research subjects were 2 expert lecturers and 1 Biology subject teacher (expert validation) and 7 students of class X IPA 1 SMA Negeri 1 Tamban (readability test). The results showed that the electronic pocket book product test was feasible to be used for material enrichment on the concept of biodiversity.